Lesão articular e resposta inflamatória no stiletto - Silva, Jamila Gomes de Oliveira (2020)
This study evaluated the presence of joint injury, muscle and inflammation in women after a stiletto class. Sixteen volunteers (23.4 ± 3.8 years; 61.7±8.1kg; 1.6±0.0m; 23.4±2.3 kg/m2; 27.2±3.8% body fat) participated in the study. The Plasma markers of joint damage (matrix metalloproteinase 3 [MMP-3]), muscle damage (myoglobin [Mb], total creatine kinase [CK] and lactate dehydrogenase [LDH]), inflammation (interleukin 8 [IL-8], tumor necrosis factor-alpha [TNF-α], interleukin 1β [IL-1β] and interleukin 6 [IL-6]) and neutrophil activation (reactive oxygen species [ROS]) were quantified before and immediately after a class of sixty minutes of class with moderate-intensity. We observed that the plasma concentration of MMP-3, Mb and CK increased by 56% (p = 0.04; d = 0.79), 113% (p = 0.007; d = 1.21) and 21% (p < 0.001; d = 0.39), respectively after class. The plasma concentration of cytokines before and after class remained similar and ROS despite the increase showed no statistical difference. We concluded that the stiletto class caused joint and muscle damage and did not alter the plasma concentration of pro-inflammatory biomarkers.